Giant cell collagenoma: Report of a rare tumor and review of literature - Biswanath Behera; Debasis Gochhait; Rashmi Kumari; Pavithra Ayyanar (Indian Journal of Pathology and Microbiology)
Giant cell collagenoma (GCC) is a rare benign dermal fibrous tumor. Although it has many clinicopathological differential diagnoses, it is often confused with cutaneous sclerotic fibroma/storiform collagenoma (SF/SC) and dermatofibroma. The following characteristic features point to GCC’s diagnosis over the latter: the presence of peculiar multinucleated giant cells, and vimentin positivity of both single and multinucleated giant cells on immunohistochemistry. Most of the reported cases have mentioned that GCC is a variant of SF/SC. We report a rare case of GCC presenting as a slow-growing solitary firm nodule over the right ankle. To the best of our knowledge, only less than ten cases have been reported, including the index case. We have also reviewed the clinicopathological features of those cases and discussed the approach to the diagnosis.